Measuring compression caused by garments. Issue 2 (20th March 2018) - Ellis, Brett; Kirkpatrick, Erin; Kothari Phan, Sonal; Imler, Stacy; Beckham, Haskell
Abstract : Purpose: Stretch fabrics are employed to create compression in garments for medical, sports, and fitness applications. Although potential correlations between wearing compression garments and physiological or performance metrics have been studied, such correlations require knowledge of the actual compression caused by garments. The purpose of this paper is to demonstrate, compare, and contrast different methods for measuring compression delivered by an exemplar compression garment. Design/methodology/approach: The exemplar compression garment is a plain jersey knit maternity band. The compression delivered by this garment was determined via three different methods – Tekscan pressure mapping system, Hohenstein Measurement System (HOSY), and a fabric-based analytical model employing uniaxial fabric tensile data. Findings: HOSY and the fabric-based model, assuming a circular cross section for the garment, provided comparable results for compression versus garment height. However, these methods did not capture the varying compression delivered at different transverse locations when the subject was noncircular in cross section. Assuming an elliptical cross section, the fabric-based model predicted results that were comparable to those measured by the Tekscan system: for example, compressions were approximately 130-160 percent greater at the hip, and approximately 60-100 percent lower at the posterior, than HOSY revealed. Further, the Tekscan system allows the effect of movement on compression to be captured. Originality/value: This paper compares and contrasts three compression measurement methods and demonstrates the importance of angular position and height dependencies. Further, the fabric-based model is presented as a tool to assist design of compression garments.